2021
DOI: 10.31338/uw.9788323548775
|View full text |Cite
|
Sign up to set email alerts
|

Polskie organizacje imigranckie w Europie. W poszukiwaniu nowego modelu

Abstract: The authors describe the situation of Polish immigrant organisations in selected European countries (Germany, France, Great Britain, Ireland, Norway, Sweden, the Netherlands, Italy and Spain) on the basis of field research. Their aim is to explore and explain the conditions under which they operate. This seminal publication presents the first cross-disciplinary research on Polish immigrant organisations. It allows to compare and generalise, enabling the authors to formulate new theoretical proposals, which aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 125 publications
0
12
0
2
Order By: Relevance
“…Do tej pory mieliśmy okazję dyskutować nad naszymi ustaleniami -szczególnie tymi opublikowanymi w monografii "Polskie organizacje imigranckie w Europie. W poszukiwaniu nowego modelu" (Nowosielski & Dzięglewski, 2021) podczas spotkań -zarówno zespołowych jak i z szerszą publicznością 5 . Dyskusje te pozwoliły nam -także dzięki krytycznym uwagom zaproszonych ekspertek i ekspertów -na wskazanie pewnych ograniczeń prowadzonych badań i wskazanie możliwych ulepszeń.…”
Section: Ograniczenia Badania I Wyzwania Na Przyszłośćunclassified
See 1 more Smart Citation
“…Do tej pory mieliśmy okazję dyskutować nad naszymi ustaleniami -szczególnie tymi opublikowanymi w monografii "Polskie organizacje imigranckie w Europie. W poszukiwaniu nowego modelu" (Nowosielski & Dzięglewski, 2021) podczas spotkań -zarówno zespołowych jak i z szerszą publicznością 5 . Dyskusje te pozwoliły nam -także dzięki krytycznym uwagom zaproszonych ekspertek i ekspertów -na wskazanie pewnych ograniczeń prowadzonych badań i wskazanie możliwych ulepszeń.…”
Section: Ograniczenia Badania I Wyzwania Na Przyszłośćunclassified
“…Rezultaty projektu były już wcześniej publikowane -przede wszystkim w monografii prezentującej jego najważniejsze ustalenia (Nowosielski, Dzięglewski, 2021), ale także w pojedynczych artykułach (m.in. Nowak, Nowosielski, 2018Nowosielski, 2021).…”
Section: O Tomieunclassified
“…The tendency for social participation to emerge in fluid organisational forms (korolczuk 2017, Dzięglewski, Nowosielski 2021) also manifests itself among Polish immigrants in Italy. As one of the interviewed experts notes:…”
Section: The Condition Of Polish Immigrant Organisations In Italymentioning
confidence: 99%
“…4 More detailed studies on the Polish community in Germany, especially in Berlin can be found in: Praszałowicz, 2010;szczepaniak-kroll, 2020. 5 immigrant organisations are defined here as associations established by and for immigrants to provide social, economic and cultural services or those which represent and seek to advance the broadly understood interests of communities (Rodriguez-Fraticelli et al, 1991). For more discussion on defining immigrant organisations see: Moya, 2005;Nowosielski & Dzięglewski, 2021.…”
Section: Introductionmentioning
confidence: 99%